Comparison of evolutionary programming and multiagent immune evolutionary programming technique in maximum loadability improvement / Mohd Reza Sulaiman - Sulaiman, Mohd Reza (2010)
This paper presents the enhancement of system load ability through optimal reactive power dispatch technique using a newly developed optimization technique, termed as Multi agent Immune Evolutionary Programming (MAIEP). The concept of MAIEP is developed based on the combination of Multi agent System (MAS), Artificial Immune System (AIS) and Evolutionary Programming (EP). In realizing the effectiveness of the proposed technique, validation is conducted on the IEEE-30-Bus Reliability Test System. The program was developed by using MATLAB software. The main propose of this project is improving load ability system by using (EP) and (MAIEP) techniques. From the result, it shows that MAIEP has faster computation time compared to EP technique in maximum load ability improvement in the system.